The Implementation of Bowen’s Theory in Family Problems - Ulya Mahmudah; Amalia Maylansari; Aqroba Ruhma (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Family therapy, as an intervention modality, serves as a professional means to address and ameliorate familial challenges through the involvement of trained experts. Within the realm of family therapy theories, Murray Bowen articulated a perspective positing the inseparability of human emotions from the environmental context. The efficacy of Bowen's family therapy approach in mitigating diverse familial issues is notable. The present study employs a systematic methodological approach, specifically relying on a comprehensive literature review derived from a selection of 15 pertinent articles spanning the years 2010 to 2023. Synthesizing findings from the literature, the Bowen theory emerges as an effective framework for addressing a spectrum of familial challenges, encompassing conflicts within couples as well as issues involving children and parents.This research show that Bowen Theory are effective in solving various families problem. Keywords: bowen, therapy, family